2014
DOI: 10.1074/jbc.m114.590430
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Selenocysteine Incorporation into the Selenium Transport Protein, Selenoprotein P

Abstract: Background: Selenocysteine incorporation into selenoprotein P (SEPP1), which contains 10 Sec residues, is unique. Results: Processive Sec incorporation can be reconstituted in vitro, independently of the conserved non-SECIS portions of the 3Ј-UTR. Conclusion: Processivity is intrinsic, but efficiency is governed by selenium levels. Significance: SEPP1 synthesis is essential for male fertility and proper neurologic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 55 publications
3
47
0
Order By: Relevance
“…Their data indicated that ribosomes that decoded one UGA as selenocysteine are more prone to decode another one. Another set of data from the group of Copeland performed in vitro, further confirms the processivity of UGA recoding (127). Interestingly, they find that other SECIS elements such as GPx4 support the processive insertion of selenocysteine, indicating an intrinsic property of the SECIS.…”
Section: The Ribosomessupporting
confidence: 53%
“…Their data indicated that ribosomes that decoded one UGA as selenocysteine are more prone to decode another one. Another set of data from the group of Copeland performed in vitro, further confirms the processivity of UGA recoding (127). Interestingly, they find that other SECIS elements such as GPx4 support the processive insertion of selenocysteine, indicating an intrinsic property of the SECIS.…”
Section: The Ribosomessupporting
confidence: 53%
“…This complex would channel efficient delivery of Sec into the ribosomal A -site thereby enhancing UGA readthrough (Small-Howard et al, 2006; Stapulionis and Deutscher, 1995). In fact, very recently selenium supplementation was demonstrated to enhance multiple but not single Sec incorporation events, further implicating a role for active aminoacylation and channeling of reactants (Shetty et al, 2014). Overall, therefore, it appears that the process of Sec incorporation is sufficient to prevent activation of the NMD pathway.…”
Section: 3 Interplay With Nonsense Mediated Decay (Nmd)mentioning
confidence: 99%
“…These findings raise additional exciting questions regarding the basic role of Sepp1 in transporting selenium to other organs, such as skeletal muscle and adipocytes, and the importance of this mechanism in energy homeostasis. One possible explanation for Sepp1 in Scly KO mice is that a truncated Sepp1 isoform is upregulated rather than a fulllength protein, as it is the case in selenium deficiency (15,57). Another possibility is that Sepp1 accumulates as a result of improper degradation due to Scly absence.…”
Section: Obesity In the Scly Ko Mousementioning
confidence: 99%